Impact of Working Capital Investment Strategies on Efficiency of Working Capital in the Pharmaceutical Industry - Kaur, Prabhpreet (Indian Journal of Finance, 2021)
The study examined the impact of working capital investment policies on the WC efficiency index in different economic situations and was based on the premise that despite having a mathematical difference in the working capital efficiencies of domestic and multinational pharmaceutical companies (DPCs and MNPCs), statistically there was no significant difference between the different periods. The analysis revealed that the majority of the companies had been practicing an aggressive working capital investment policy. Similarly, the difference between the efficiencies and investment policies of DPCs and MNPCs was also not statistically significant. The regression coefficients found in the study provide directions to managers to reduce the ratio of aggressive investment policy and conservative investment policy and enhance the working capital efficiency during the boom period. The negative coefficients of correlation also supplemented this finding. The value of R-square showed that the major variations in the efficiency index during the boom period were caused by investment policies. During recession and recovery periods, because of positive beta coefficients, the management of the DPCs should infuse more investments in current assets.